Incremental value of preoperative right ventricular function in predicting moderate to severe acute kidney injury after heart transplantation - Zhu, Shuangshuang; Zhang, Yanting; Qiao, Weihua; Wang, Yixuan; Xie, Yuji; Zhang, Xin; Wu, Chun; Wang, Guohua; Li, Yuman; Dong, Nianguo; Xie, Mingxing; Zhang, Li (Frontiers in Cardiovascular Medicine, 2022)
Background Acute kidney injury (AKI) commonly occurs after heart transplantation (HTx), but its association with preoperative right ventricular (RV) function remains unknown. Consequently, we aimed to determine the predictive value of preoperative RV function for moderate to severe AKI after HTx. Materials and methods From 1 January 2016 to 31 December 2019, all the consecutive HTx recipients in our center were enrolled and analyzed for the occurrence of postoperative AKI staged by the Kidney Disease: Improving Global Outcomes (KDIGO) criteria. Conventional RV function parameters, including RV fractional area change (RVFAC) and tricuspid annular plane systolic excursion (TAPSE), were obtained. The primary endpoint was moderate to severe AKI (the KDIGO stage 2 or 3). The secondary endpoints included the impact of AKI on intensive care unit (ICU) mortality, in-hospital mortality, and 1-year mortality. Results A total of 273 HTx recipients were included in the study. Postoperative AKI occurred in 209 (77%) patients, including 122 (45%) patients in stage 1 AKI, 49 (18%) patients in stage 2 AKI, and 38 (14%) patients in stage 3 AKI. Patients with higher AKI stage had lower baseline estimated glomerular filtration rate (eGFR), more frequent diabetes, higher right atrial pressure (RAP), longer cardiopulmonary bypass (CPB) duration, more perioperative red blood cell (RBC) transfusions, and worse preoperative RV function. A multivariate logistic regression model incorporating previous diabetes mellitus [odds ratio (OR): 2.21; 95% CI: 1.06–4.61; P = 0.035], baseline eGFR (OR: 0.99; 95% CI: 0.97–0.10; P = 0.037), RAP (OR: 1.05; 95% CI: 1.00–1.10; P = 0.041), perioperative RBC (OR: 1.18; 95% CI: 1.08–1.28; P < 0.001), and TAPSE (OR: 0.84; 95% CI: 0.79–0.91; P < 0.001) was established to diagnose moderate to severe AKI more accurately [the area under the curve (AUC) = 79.8%; Akaike information criterion: 274]. Conclusion Preoperative RV function parameters provide additional predicting value over clinical and hemodynamic parameters, which are imperative for risk stratification in patients with HTx at higher risk of AKI.